PENGARUH MODEL PEMBELAJARAN SFE (STUDENT FACILITATOR AND EXPLAINING BERBANTUAN MEDIA CANVA TERHADAP KEMAMPUAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS X SMA NEGERI 1 SEI BALAI - Sri Liana; Karimaliana Karimaliana (STKIP Pesisir Selatan, 2026)
This study aims to determine the effect of the SFE (Student Facilitator and Explainer) learning model using Canva on the writing skills of observational report texts among tenth-grade students at SMA Negeri 1 Sei Balai in the 2025/2026 academic year. The problem in this study is the students' low ability to write observational report texts, particularly in understanding the structure of general statements, section descriptions, and appropriate benefit theses. This study used a quantitative experimental method using a posttest-only control group design. The population was all 150 tenth-grade students at SMA Negeri 1 Sei Balai. The control class's average score was 68.33, categorized as good, while the experimental class's average score was 80.5, categorized as good. Based on the results of the hypothesis test using the t-test, it was obtained that (t_count > t_table), , which is 5.45 > 1.67, then the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Then at a significance level of 1% with dk = 58, it was obtained that ????ℎ????????????????????>????????????????????????, which is 5.45 > 2.39, so the null hypothesis (Ho) which states there is no significant effect is rejected and the alternative hypothesis (Ha) which states there is a significant effect of the use of Canva media on the ability to write observational report texts in class X students of SMA Negeri 1 Sei Balai in the 2025/2026 academic year is accepted.